CEDA dredging days 1987 proceedings : during Europort 87 Exhibition 10/11 November 1987. (Thomas Telford, 1987)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in 1987.